Low Permeability Concrete for Buildings Located in Marine Atmosphere Zone using Clay Brick Powder. Issue 1 (February 2020) - Castillo, M; Hernández, K; Rodriguez, J; Eyzaguirre, C
Abstract: The concrete is not one hundred percent impermeable since the water that remains inside it causes its corrosion, in the case of reinforced concrete, exposed in an area of marine atmosphere, the sea salt mostly present in large particles of the marine spray, produce the reduction of the alkalinity of the concrete causing a rapid corrosion of the steel. There are buildings built in this marine area that have been designed without durability criteria, in which the use of pozzolanic materials is considered, for example, to fill the pores of the cement matrix and thus guarantee its impermeability. In the present study, the effect of clay brick powder (PLA) as a replacement for cement in concrete manufacturing is addressed, evaluating different characteristics of its components. The results indicate that pozzolanic activity and compressive strength increase, slump, voids content and the coefficient of permeability to water decreases.